Application of an innovative high-throughput liquid chromatography-tandem mass spectrometry method for simultaneous analysis of 18 hazardous drugs to rule out accidental acute chemotherapy exposures in health care workers. (June 2020) - Shu, Pan; Zhao, Ting; Wen, Bo; Mendelsohn-Victor, Kari; Sun, Duxin; Friese, Christopher R; Pai, Manjunath P
Objectives: Despite safe handling guidelines published by several groups, health care worker exposure to hazardous drugs continues to occur due to suboptimal engineering controls and low use of protective equipment. Simple, multi-target and specific analytical methods are needed so that acute exposures to these drugs in the workplace can be assessed rapidly. Our aim was to develop an analytical method for simultaneous detection and quantification of widely used cancer drugs to rule out accidental acute chemotherapy exposures in health care workers. Methods: We examined the feasibility of alternate high-performance liquid chromatographic-tandem mass spectrometry methods to simultaneously detect eighteen chemotherapy analytes in plasma and urine. The linear concentration ranges tested during assay development were 0.1–50 ng/mL. After development of a multi-analyte assay protocol, plasma samples (n = 743) from a multi-center cluster-randomized clinical trial (n = 12 sites) of an hazardous drug educational intervention were assayed. Confirmatory assays were performed based on the individual acute-spill case-histories. Results: An innovative HPLC-multiple reaction monitoring-information dependent acquisition-enhanced production ion (MRM-IDA-EPI) analytical method was developed to simultaneously detect: cytarabine, gemcitabine, dacarbazine, methotrexate, topotecan, mitomycin, pemetrexed, irinotecan, doxorubicin, vincristine, vinblastine, ifosamide, cyclophosphamide, vinorelbine, bendamustine, etoposide, docetaxel, and paclitaxel. The retention times ranged from 4 min to 13 min for the analytical run. The limit of detection (MRM-IDA-EPI) and limit of quantitation (MRM) was 0.25 ng/mL and 0.1 ng/mL, respectively for most analytes. No detectable plasma concentrations were measured at baseline, post-intervention and in cases of documented acute spills. Use of a secondary tandem mass spectrometry approach was able to successfully rule out false positive results. Conclusions: Development of a sensitive high-throughput multi-analyte cancer chemotherapy assay is feasible using an MRM-IDA-EPI method. This method can be used to rapidly rule out systemic exposure to accidental acute chemotherapy spills in health care workers.